Diversity-oriented TsOH catalysis-enabled construction of tanshinone-substituted bis(indolyl/pyrrolyl)methanes and their biological evaluation for anticancer activities. Issue 24 (17th December 2017) - Liu, Xiong-Wei; Chen, Zhi-Yong; Wang, Guan-Lian; Ma, Xi-Tao; Gong, Yi; Liu, Xiong-Li; Feng, Ting-Ting; Zhou, Ying
ABSTRACT: We have developed an efficient and straightforward methodology for the synthesis of novel tanshinone-substituted bis(indolyl/pyrrolyl)methane scaffolds3 through TsOH catalysis-enabled addition of indoles or pyrroles1 with tanshinones2 based on molecular hybridization strategy. Products were smoothly obtained in good yields (up to 81% yield). This protocol also represents the first construction of tanshinone skeleton-fused bis(indolyl/pyrrolyl)methane scaffolds, thus leading to new knowledge in the fields of both molecular complexity and diversity-oriented synthesis and the lead compound discovery. Furthermore, their biological activities against human leukemia cells K562, human prostate cancer cells PC-3, and human lung cancer cells A549 have been preliminarily demonstrated by in vitro assays. The results demonstrated that most of these compounds3 obtained by this protocol showed comparable activity to the positive control of cisplatin. GRAPHICAL ABSTRACT: